USE OF APPLICATION BASED MODULE ON ADDITIVE AND ADDICTIVE MATERIALS FOR LEARNING ACTIVITIES DURING PANDEMIC COVID -19 (Study at a Student of Junior High School Muhammadiyah 1 Sleman) - Rakhmiyati (Proceeding International Conference on Science and Engineering, 2021)
Abstract: The use of modules as a medium for learning at the school level is commonly used. The module serves to assist educators in delivering material. Therefore, the module must have good quality in terms of material and design so that students can more easily understand the material presented. At this time, the module is expected to be able to help students understand the material, because during the Covid-19 pandemic, students were asked to do learning activities at home. The material is delivered by the teacher online through the WhatsApp group during the learning hours. This study examines the material additives and addictive substances delivered to class VIII students. The object of this research is the VIII grade students of junior high school Muhammadiyah 1 Sleman which consists of three classes. The purpose of this study was to determine the level of students’ understanding of additives and addictive substances.